Analisis Kelayakan Usaha Tani Komoditi Pisang Cavendish Di Desa Kuniran Kecamatan Purwosari Kabupaten Bojonegoro - Hardiyanto, Eko; Surjono, Surjono; Prayitno, Gunawan (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The Cavendish banana s one of the commonly widely cultivated and commercial banana commodities in Indonesia and more than 40% of the fruit is produced worldwide. Reviewed from a market perspective, this commodity is so potential that it offers an opportunity to increase its productivity in meeting the needs of the market. The research was conducted in the village of Kuniran, Purwosari district of Bojonegoro. This research is quantitative and descriptive taking samples of 10 farmers who belonged to UD. Agro Kurnia (the population). The determination of samples used a purposive sampling method. This study aims to analyze the viability of cavendish bananas cultivated by UD. Kurnia Agrosâ€™s farmers, cover a total of 1500 trees on 1.8 ha of land. The research was carried out from August to December 2023. The data collection method uses PRA livelihood assessment tools, input and output flow charts, and garden sketches. The results of this study showed that the total expenditure of Rp. 18,210,000, farmers received a total receipt of Rp. 72,200,000 in one season. Total receipts were deducted from the total cost and the total revenue was Rp. 57,615,000.00 in one harvest season. The value of the R/C ratio was >1, which means that the total income was greater than the total costs so the cultivation of cavendish banana commodities at the village of Kuniran is very profitable and worthy of being continued and developed.Â